Levels of Stress, Anxiety, and Depression in Tourism Workers in the Bali Province During the COVID-19 Pandemic - Nadarin, Anak Agung Sagung Ayu Tribhuwana Wulan; Apsari, Putu Indah Budi; Wijaya, Made Indra (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Stress, anxiety, and depression in tourism workers have increased during the COVID-19 pandemic, which are mental health problems that need to be watched out for. Mental health has become one of the most significant problems in the world, including Indonesia, especially during the COVID-19 pandemic. Seeing the significant role of mental health disorders in tourism workers accompanied by stress, anxiety, and depression can have an impact on the health of human resources in the tourism sector. The purpose of this study was to determine the level of stress, anxiety, and depression in tourism workers in the province of Bali during the COVID-19 pandemic. The sample of this study was 103 people aged 18-60 years who are active tourism workers in the Province of Bali, which was selected by convenience sampling using Google Forms. The research method was cross-sectional and analyzed using SPSS version 27. The study results showed that most of the research samples experienced severe stress, as many as 38 (36.9%). The majority of the study sample experienced very severe anxiety with 74 people (71.8%). Most of the research samples experienced very severe depression, with 65 respondents (63.1%). In conclusion, tourism sector workers suffer severe stress, anxiety, and depression during the COVID-19 pandemic.